2012
DOI: 10.1074/mcp.m111.012088
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Conformation of the ISWI ATPase Domain With Genetically Encoded Photoreactive Crosslinkers and Mass Spectrometry

Abstract: We present a strategy for rapidly gaining structural information about a protein from crosslinks formed by genetically encoded unnatural amino acids. We applied it to ISWI, a chromatin remodeling enzyme involved in chromatin assembly, DNA replication and transcription. ISWI is part of the vast Snf2 family of helicase-related proteins, many of which constitute the catalytic cores of chromatin remodeling complexes. Structural information about this family is scarce, hampering our mechanistic understanding of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…UV light activates Bpa to cross-link nearby alkyl carbons with a preference for aliphatic residues (10). Bpa substitutions provide highly specific cross-linking information that can resolve unique binding partners in nearby features (11). We tested each purified, radiolabeled variant for cross-linking to RNAP holoenzyme in vitro, identifying 18 variants that cross-linked to one of the two large subunits in RNAP (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…UV light activates Bpa to cross-link nearby alkyl carbons with a preference for aliphatic residues (10). Bpa substitutions provide highly specific cross-linking information that can resolve unique binding partners in nearby features (11). We tested each purified, radiolabeled variant for cross-linking to RNAP holoenzyme in vitro, identifying 18 variants that cross-linked to one of the two large subunits in RNAP (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…Data Analysis-Mass spectrometry data from the crosslinked PTEN samples were analyzed using Crossfinder version 1.0 (20,21) with the default parameters. Prior to analysis with Crossfinder, MS/MS data were converted to mzXML files using ProteoWizard.…”
Section: Methodsmentioning
confidence: 99%
“…Irradiation of BB-4p-PTEN was followed by alkaline phosphatase treatment (to remove the mass spectrometry electrospray ionization suppressive effects of the phosphates) and trypsinization and avidin treatment to enrich for biotin-containing peptides. These peptides were then subjected to LC-MS/MS, and then the data were analyzed using Crossfinder (20,21). This led to the identification of a cross-linked peptide that contained a C-terminal peptide ( 379 CSDTTDSD-PENEP(B)DEDK bio 396 ) attached to an N-terminal peptide ( 42 LEGVYRNNIDDVVR 55 ) (Fig.…”
Section: Individual Tail Phosphorylation Effects On Ptenmentioning
confidence: 99%
“…Probing the conformation of the ISWI ATPase domain with genetically encoded photoreactive cross-linkers and mass spectrometry allowed us to take advantage of the UV-reactive p-benzoyl-p-phenylalanine. It could be shown that the ATPase lobes strongly rotate against each other, a movement postulated earlier to be necessary to achieve a catalytically competent state (Forne et al 2012).…”
Section: Biohybrid Systems: Modifying Proteins Containing Unnatural Amentioning
confidence: 99%